Developing the Market for Local Currency Bonds by Foreign Issuers: Lessons from Asia - Tobias C. Hoschka (Asian Development Bank (ADB), 2005)
This paper surveys the experience of countries in the East Asian region that have introduced local currency bonds by foreign issuers. The countries that are examined include Australia; Hong Kong, China; Japan; Republic of Korea; and Singapore. It is suggested that there are sound reasons for many countries to develop the market for foreign issuers. Benefits and potential issues are analyzed, development policies are reviewed, and concrete policy options are discussed for those countries that are currently considering opening their domestic markets to foreign issuers.
hdl:11540/1893
Keywords: 330; Rentenmarkt; Öffentliche Anleihe; Internationale Anleihe; Australien; Hongkong; China; Japan; Südkorea; Singapur